2009
DOI: 10.1038/tpj.2009.16
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of CYP2C9 polymorphisms in the south of Europe

Abstract: CYP2C9 is a major liver enzyme responsible of the metabolism of many clinically important drugs. The presence of CYP2C9 genetic polymorphisms has been associated with marked interindividual variability in its catalytic activity that could result in drug toxicity. Here we present frequencies of the most common CYP2C9 coding variants CYP2C9*2 (C430T) and CYP2C9*3 (A1075C) in representative samples of four regions from Spain (Basque Country, n ¼ 358; Catalonia, n ¼ 240; Central Spain, n ¼ 190 and Galicia, n ¼ 288… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…In addition, the SP population studied here presented similar CYP2C9 allele frequencies to those previously reported in a recent publication of frequencies found in northern regions of South Europeans. 11 Furthermore, the frequency of CYP2C9*3 was lower (Po0.05) in MT (0.015) and MM (0.015) than in MA (0.06) and SP (0.08).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, the SP population studied here presented similar CYP2C9 allele frequencies to those previously reported in a recent publication of frequencies found in northern regions of South Europeans. 11 Furthermore, the frequency of CYP2C9*3 was lower (Po0.05) in MT (0.015) and MM (0.015) than in MA (0.06) and SP (0.08).…”
Section: Resultsmentioning
confidence: 90%
“…In addition, the present Spanish population from Extremadura appeared very representative, as it was found to be very similar in CYP2C9 allele frequencies to previously published data of White Europeans. 11,13,14 Clinical implications for patients carrying the low activity alleles CYP2C9*2 and CYP2C9*3 have been reported. Patients who are CYP2C9 'slow metabolizers', mostly *3/*3 carriers, and are under treatment with some narrow therapeutic index drugs (warfarin, acenocoumarol, glipizide, and phenytoin) may be at risk of severe drug toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Two dominant variants, CYP2C9*2 and CYP2C9*3, are common in Caucasians at frequencies of approximately 8%-14% and 4%-16%, respectively, while significantly lower frequencies of these variants were found in African and Asian populations [4,5] . A large-scale genetic polymorphism study revealed that approximately 40% of Europeans carry these two mutated alleles [6] . In contrast, the *2 variant is rarely found, and the *3 variant is present in only at 1%-4% of East Asian populations [7,8] , and our previous study demonstrated that only 0.28% and 5.6% of Chinese people carry the CYP2C9*2 or CYP2C9*3 allele, respectively [9] .…”
Section: Introductionmentioning
confidence: 99%
“…7 However, 29.4% of patients had the CYP2C9*2 variant allele and 11.4% had the CYP2C9*3 variant allele, which are similar prevalences to those described for Spanish patients previously. 19,20 In previous studies, polymorphisms of both genes have been shown to be associated with adverse events and with a poor TTR in patients taking VKAs. 21 Thus, the presence of variant genotypes of CYP2C9 (*2 and *3) and VKORC1 (rs9923231 and rs9934438) is associated with increased risk of bleeding in warfarin users.…”
Section: Discussionmentioning
confidence: 98%
“…ROC curves comparisons were carried out by DeLong et al method. 12 Net reclassification improvement (NRI) and integrated discriminatory improvement (IDI) were performed according to the methods described by Pencina et al 13 Statistical analyses were performed using SPSS v. 19.0 (SPSS, Inc., Chicago, IL, USA) and MedCalc v. 16…”
Section: Discussionmentioning
confidence: 99%